2007
DOI: 10.1093/jnci/djk029
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Infarction Mortality Risk After Treatment for Hodgkin Disease: A Collaborative British Cohort Study

Abstract: The risk of death from myocardial infarction after treatment for Hodgkin disease remains high for at least 25 years. The increased risks are related to supradiaphragmatic radiotherapy but may also be related to anthracycline and vincristine treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
220
0
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 406 publications
(237 citation statements)
references
References 17 publications
7
220
0
10
Order By: Relevance
“…Several studies of cause‐specific mortality in survivors of Hodgkin lymphoma diagnosed in childhood or early adult life have been carried out,19, 20, 21 and the risk of hospitalisation among survivors of all types of cancer diagnosed in adolescence and young adulthood has been studied in other populations 22, 23, 24, 25. Other studies specifically of survivors of Hodgkin lymphoma diagnosed in young adulthood have usually reported on specific risks of second cancers11, 26, 27, 28, 29, 30, 31, 32, 33 or cardiovascular diseases 12, 34, 35, 36. The results of our study are in agreement with their findings.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of cause‐specific mortality in survivors of Hodgkin lymphoma diagnosed in childhood or early adult life have been carried out,19, 20, 21 and the risk of hospitalisation among survivors of all types of cancer diagnosed in adolescence and young adulthood has been studied in other populations 22, 23, 24, 25. Other studies specifically of survivors of Hodgkin lymphoma diagnosed in young adulthood have usually reported on specific risks of second cancers11, 26, 27, 28, 29, 30, 31, 32, 33 or cardiovascular diseases 12, 34, 35, 36. The results of our study are in agreement with their findings.…”
Section: Discussionmentioning
confidence: 99%
“…7,22,23 Two recent large cohort studies from the Netherlands and UK show an increased standardized mortality rate in CVD that is probably attributed to radiotherapy and adriamycin. 5,4 The UK study also found a significant relation to vincristin. 4 The Dutch study, which was a matched control study, found that there was a general increase in the risk for in patient care for CVD in patients treated for HL.…”
Section: Discussionmentioning
confidence: 86%
“…5,4 The UK study also found a significant relation to vincristin. 4 The Dutch study, which was a matched control study, found that there was a general increase in the risk for in patient care for CVD in patients treated for HL. 5 The comorbidity question could be answered by the prospective study as information of HL treatment and family history of CVD are collected.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations